Cue-Responding Behaviors During Pharmacy Counseling Sessions With Patients With Asthma About Inhaled Corticosteroids: Potential Relations With Medication Beliefs and Self-Reported Adherence. Issue 10 (2nd October 2016) - Driesenaar, Jeanine A.; De Smet, Peter A. G. M.; van Hulten, Rolf; Noordman, Janneke; van Dulmen, Sandra
ABSTRACT: The aim of this study was to examine cue-responding behavior at the pharmacy while counseling about inhaled corticosteroids (ICS) in relation to medication adherence and medication beliefs. Patients with asthma aged ≥18 years using ICS were recruited from 12 pharmacies. Counseling sessions were video-recorded. Patients' emotional and informational cues and pharmacists' and pharmacy technicians' cue-responding behaviors were coded using an expanded version of the Medical Interview Aural Rating Scale. The Beliefs about Medicines Questionnaire assessed patients' ICS concern and necessity beliefs. Self-reported ICS adherence was measured by four questions. During the 86 sessions, patients expressed on average 2.3, mostly informational, cues (70.8%). In 26.7% of the sessions, no cues were expressed. Pharmacists' and technicians' responses to emotional cues (59.3%) were mostly inadequate, and to informational cues mostly appropriate (63.6%). Providing inappropriate information (20.3%) was related to higher concerns post session ( p < .05), and cue exploration to higher self-reported adherence at 3 months ( p < .05). Apparently, providers' responses to patients' cues might have therapeutic value. In addition, patients might need to be encouraged to ask questions and express their concerns.